2019
DOI: 10.1186/s41100-019-0211-1
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported intra-dialytic symptoms and post-dialysis recovery times are influenced by psychological distress rather than dialysis prescription

Abstract: Background: Dialysis is a life-sustaining treatment, but many patients suffer symptoms during dialysis and take time to recover. Previous reports have linked recovery time to intra-dialytic hypotension and rapid solute clearances, whereas others have reported an association with psychological factors. As such, we wished to investigate which factors were important in determining symptom self-reporting and delayed recovery times. Methods: We recorded self-reported patient intra-dialytic symptoms, recovery times … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 37 publications
(61 reference statements)
2
10
0
1
Order By: Relevance
“…A prolonged recovery time affects both the patients and the healthcare professionals or caregivers. Thus, determining the modifiable treatment-related factors has received increasing attention [5][6][7][8][9][10][11][12][13]. In our country, there are not any previous studies on this particular matter.…”
mentioning
confidence: 99%
“…A prolonged recovery time affects both the patients and the healthcare professionals or caregivers. Thus, determining the modifiable treatment-related factors has received increasing attention [5][6][7][8][9][10][11][12][13]. In our country, there are not any previous studies on this particular matter.…”
mentioning
confidence: 99%
“…[ 17 ] had not found any significant association between recovery time and other variables. Another study done by Yoowannakul[ 23 ] et al . showed that younger patients had prolong recovery time than elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies gave conflicting results regarding the associated factors with DRT. [ 18 22 23 24 25 ] Multicentric studies including a larger sample size in Indian HD patients may be needed to find out the other significant variables that predict DRT.…”
Section: Discussionmentioning
confidence: 99%
“…Patient-centered care in dialysis requires a multifaceted approach to better understand influential patient factors 5 and incorporation of patients’ perspectives routinely into structured care delivery. 6 Dialysis metrics have historically focused on urea kinetics, hospitalization rates and mortality, vascular access, other biochemical results such as serum calcium level, and infectious complications.…”
mentioning
confidence: 99%
“… 11 For instance, depression has been linked to an increase in symptom perception and reporting among the elderly. 13 Among dialysis patients, increased self-reported psychological distress is associated with greater dialysis-related symptom burden, 5 and higher self-reported depression scores are associated with increased dialysis recovery time. 7 The scale used by Alvarez et al would have been strengthened by the inclusion of a psychological assessment such as psychological distress, anxiety, or situational fear.…”
mentioning
confidence: 99%